EXISTENCE OF INTENTION AND CLASSIFICATION OF SPIRITUAL QUALITY OF STUDENTS AT THE BOARDING SCHOOL JAGAD ALIMUSSIRRY SURABAYA - Aini, Siti Nur; Syarifuddin, Ahmad (Journal Intellectual Sufism Research (JISR), 2018)
Scientific writing aims to find out the intentions and sincerity correctly, efforts must be made to improve the spiritual quality of students. This research is a qualitative analysis research with case study method. Data collection techniques used are observation, interviews, and documentation. Data sources came from the Jagad Alimussirry Student Boarding School. The results of the analysis show that something done with intention and sincerity only gives to God so that it becomes a perfect charity from one's worship. Before charity must be careful so that the charity that is done can be accepted by God. People who purify the heart of all defilements by avoiding evil, maintain honesty in words and deeds, their hearts will become clean, can emit positive energy and can meet Allah SWT.